Incidence of different kinds of reproductive disorders in livestock - PANDIT, R K (The Indian Journal of Animal Reproduction, 2023)
Of the 8327 cases attended during ten years period in the poly clinic, 3127 were from reproduction discipline. The monthwise analysis of the incidence of the occurrence of the cases indicated variability between the months. The maximum occurrence (53 .15%) was of anoestrus cases. Pregnancy was confirmed in 904 cows and buffaloes. Repeat breeding was observed in 25 cows and 8 buffaloes. The miscellaneous type of cases were pyometra, endometritis, cervicitis and infantile genitalia. Castration was performed in 231 cattle and 183 goats. In cattle and buffaloes, more than 75 % pregnancies were recorded in right horn.